2013
DOI: 10.1364/ao.52.004097
|View full text |Cite
|
Sign up to set email alerts
|

Study of reference waves in single-exposure generalized phase-shifting digital holography

Abstract: The appropriate reference wave in single-exposure phase-shifting digital holography using a random-complex-amplitude encoded reference wave is experimentally investigated. Although the reference wave is generalized, the quality of reconstructed images depends on it. Furthermore, when the reference wave satisfies a certain condition, reconstructed images cannot be obtained in this method. After the certain condition is presented, the appropriate condition is studied using a speckle property. Experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Phase-shifting digital holography with a tri-focal Fibonacci telescope in a single exposure Yingge Zhang 1,4 , Yaocun Li 2,3,4 , You Li 2,3 , Ailing Tian 1 and Junyong Zhang 2 the optical detector [15]. Nomura proposed a single-exposure phase-shifting technique with a random phase reference beam [16]. The whole process requires two frames of interferograms, one of which corresponds to the interference pattern between the object and reference beams with the other being a random phase interferogram; the two holograms are then calculated and synthesized in a computer.…”
Section: Laser Physicsmentioning
confidence: 99%
“…Phase-shifting digital holography with a tri-focal Fibonacci telescope in a single exposure Yingge Zhang 1,4 , Yaocun Li 2,3,4 , You Li 2,3 , Ailing Tian 1 and Junyong Zhang 2 the optical detector [15]. Nomura proposed a single-exposure phase-shifting technique with a random phase reference beam [16]. The whole process requires two frames of interferograms, one of which corresponds to the interference pattern between the object and reference beams with the other being a random phase interferogram; the two holograms are then calculated and synthesized in a computer.…”
Section: Laser Physicsmentioning
confidence: 99%
“…To avoid the use of a special phase-shifting device, single-exposure phase-shifting digital holography using a random-complexamplitude encoded reference wave was proposed. The amplitude and phase of the reference wave are generalized in the algorithm [18]. Advances in science and technology to meet challenges Figure 3 shows the progress in digital holography.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…Nomura et al demonstrated that the object’s wavefront can be recovered by interference with a random-phase reference wave [186188]. However, the phase of the reference wave must be measured a priori .…”
Section: Snapshot Multidimensional Imaging Implementations and Appmentioning
confidence: 99%